Precision Penning-trap measurement to investigate the role of the 51Cr(e−,νe)51V Q value in the gallium anomaly - Macdonald, Tegan; Schultz, B. E.; Bale, J. C.; Chaudhuri, A.; Chowdhury, U.; Frekers, Dieter; Gallant, Aaron; Grossheim, A.; Kwiatkowski, A. A.; Lennarz, A.; Simon, Martin C.; Simon, Vanessa Véronique; et al. (Physical review. C, Nuclear physics, 2014)
A direct Q-value measurement has been made at TRIUMF's Ion Trap for Atomic and Nuclear Science (TITAN) for the 51Cr(e−,νe)51V reaction. This electron capture (EC) reaction was used in calibration measurements at the solar neutrino experiments SAGE and GALLEX, and the observed event rate differed from predictions creating the so-called gallium anomaly. Using isotopes delivered by the Isotope Separator and Accelerator (ISAC) facility at TRIUMF and charge breeding them to charge states 5+ and 6+, a Q value of 751.86(55) keV was determined. This represents a 1.3σ deviation from the result in the Atomic Mass Evaluation 2012 (AME12) and the value used in the calculated event rate. This deviation is found to be insignificant in context of the gallium anomaly, thus confirming that the predicted event rate has not been overestimated as the result of an erroneous 51Cr EC Q value. Additionally, the absolute masses of each 51Cr and 51V have been independently determined and are in agreement with the AME12 values.